2009
DOI: 10.1037/a0017391
|View full text |Cite
|
Sign up to set email alerts
|

The YouthMood Project: A cluster randomized controlled trial of an online cognitive behavioral program with adolescents.

Abstract: The aim in the current study was to investigate the effectiveness of an online, self-directed cognitive-behavioral therapy program (MoodGYM) in preventing and reducing the symptoms of anxiety and depression in an adolescent school-based population. A cluster randomized controlled trial was conducted with 30 schools (N = 1,477) from across Australia, with each school randomly allocated to the intervention or wait-list control condition. At postintervention and 6-month follow-up, participants in the intervention… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
332
2
7

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 287 publications
(351 citation statements)
references
References 53 publications
10
332
2
7
Order By: Relevance
“…Therefore, despite a relatively steady stream of research identifying the positive impact technology can have on mental health outcomes [17] [18] [40]- [46], the attitudes of clinicians in their willingness to engage young people through ICT does not appear to be changing quickly. Much of this earlier research was focused primarily on self-help computerized programs [17] [43] [45] [46] and it is possible that to date clinicians have tried to largely ignore these new therapeutic options, or, have seen them as completely separate resources to be used as an adjunct to therapy and therefore, are not interfering with their current service approach. The current research however appears to be particularly concerning for mental health professionals who now fear that ICT could be encroaching upon their specialized skill set.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, despite a relatively steady stream of research identifying the positive impact technology can have on mental health outcomes [17] [18] [40]- [46], the attitudes of clinicians in their willingness to engage young people through ICT does not appear to be changing quickly. Much of this earlier research was focused primarily on self-help computerized programs [17] [43] [45] [46] and it is possible that to date clinicians have tried to largely ignore these new therapeutic options, or, have seen them as completely separate resources to be used as an adjunct to therapy and therefore, are not interfering with their current service approach. The current research however appears to be particularly concerning for mental health professionals who now fear that ICT could be encroaching upon their specialized skill set.…”
Section: Discussionmentioning
confidence: 99%
“…At one end of the involvement spectrum are pure self-help programs with no therapist input, whereas at the other end are programs requiring considerable therapist contribution or oversight. Early dropping out from treatment has been high in some studies (Melville et al 2010) especially from entirely self-directed or open access Web-based interventions (Calear et al 2009). Conversely, support of e-therapy by a clinician can improve adherence (Christensen et al 2004) and efficacy (Andersson and Cuijpers 2009) for adults.…”
Section: Therapist Involvementmentioning
confidence: 99%
“…However, MoodGYM has been tested universally in a large school-based trial and has shown promise of effectiveness in the prevention of the development of depressive symptoms (Calear et al 2009) and, on the other hand, an online program CATCH-IT has been demonstrated to reduce vulnerability to depression as well as reducing current depressive symptoms (Van Voorhees et al 2009). Recent meta-analyses suggest that depression prevention programs (usually delivered by teachers or health professionals in classrooms) may reduce the onset of depressive disorders, hence the development and testing of computerized interventions for prevention may be a promising way forward (Merry 2014).…”
Section: From Treatment To Preventionmentioning
confidence: 99%
“…However, these low recruitment rates may not be unusual for a fully online intervention and may be consistent with the finding that only 10 to 20 percent of adults are interested in an Internet-based lifestyle change at any given time [45][46]. Furthermore, the moderate depression pre/post ESs were less than those seen in treatment interventions involving therapist and discussion group contact (VETS PRE-VAIL ES = 0.45 vs Internet plus therapist contact ES = 0.93) [21,[47][48] but comparable with preventive interventions using an Internet-only approach (male adolescents ES = 0.29) [47,49]. Similarly, this intervention demonstrated pre/post ESs comparable to an Internet-only PTSD intervention but lower than those reported in one with therapist contact (VETS PREVAIL ES = 0.30 vs ES = 0.45 for Internet-only or ES = 0.76 for Internet plus therapist) [50][51].…”
Section: Discussionmentioning
confidence: 98%